Pelatihan Menulis Skenario Untuk Siswa SMA Negeri 7 Pekanbaru - Evizariza Evizariza; Muhammad Kafrawi (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2022)
Abstract It is undeniable that the development of sophisticated communication technology requires human resources, especially the creative young generation, who are ready to take advantage of technology. One of the advancements in communication technology is social media which provides a variety of content in the form of writing, photos, and videos. Especially video social media content, be it YouTube, Facebook, Tiktok, or Instagram, the expertise to plan to produce videos that attract writing skills. Writing a screenplay is an absolute requirement to produce a good video work, in this case a film, so it is necessary to train screenwriters among the younger generation. This scenario writing training focused on students of SMA Negeri 7 Pekanbaru. The choice of SMA Negeri 7 Pekanbaru as the place for this writing training was taken considering that SMA Negeri 7 Pekanbaru is very active in producing works of art, especially works of art related to acting (theater). Keywords: Scenario, Writing, Students